Electronic Properties of Boron and Silicon Doped (10, 0) Zigzag Single-Walled Carbon Nanotube upon Gas Molecular Adsorption: A DFT Comparative Study. (29th December 2013) - Gowri sankar, P. A.; Udhayakumar, K.
Abstract : We have performed a comparative study of nine predominant gas molecules (H2, H2 O, O2, CO, CO2, NO, NO2, NH3, and CH3 OH) adsorption property on the top surface of the (10, 0) zigzag single-walled pristine Carbon nanotube (C-CNT), Boron doped carbon nanotube (B-CNT), and Silicon doped carbon nanotube (Si-CNT) are investigated by using density functional theory (DFT) computations to exploit their potential applications as gas sensors. For the first time, we calculated the optimal equilibrium position, absorption energy (E ad ), and density of states (DOS) of the considered gas molecules adsorbed on the open end of zigzag single-walled (10, 0) B-CNT and Si-CNT. Our first principle calculations demonstrate that the B-CNT and Si-CNT adsorbent materials are able to adsorb the considered gas molecules with variety of adsorption energy and their electronic structure dramatic changes in the density of states near the Fermi level. The obtained comparative DFT studies results are useful for designing a high-fidelity gas sensor materials and selective adsorbents for a selective gas sensor.